2017
DOI: 10.21831/jpv.v7i1.12879
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan media pembelajaran kearsipan digital untuk meningkatkan hasil belajar siswa SMK Negeri 3 Surakarta

Abstract: Abstrak Penelitian ini bertujuan untuk mengetahui kefektifan media pembelajaran kearsipan digital dalam meningkatkan hasil belajar siswa SMK Negeri 3 Surakarta. Penelitian ini merupakan penelitian dan pengembangan (R & D). Model pengembangan media ini menggunakan model THE DEVELOPMENT OF LEARNING MEDIA ARCHIVES TO IMPROVE STUDENT LEARNING OUTCOMES SMK NEGERI 3 SURAKARTA Abstract This study aims to determine the effectiveness of instructional media digital archives in improving student learning outcomes SMK Neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
1
6
0
7
Order By: Relevance
“…Arnanto & Triyono's (2014) study revealed that the internet-assisted teaching in VHSs in Yogyakarta City is already effective, although for the mastery of teaching strategies teachers need to improve themselves by attending trainings related to the internet-assisted teaching. Moreover, Wirawan, Indrawati, & Rahmanto (2017) having developed a learning media archives to improve student learning outcomes of the Vocational High School 3 of Surakarta stated a conclusion of their study that the development of instructional media digital archives is considered effective in improving student learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Arnanto & Triyono's (2014) study revealed that the internet-assisted teaching in VHSs in Yogyakarta City is already effective, although for the mastery of teaching strategies teachers need to improve themselves by attending trainings related to the internet-assisted teaching. Moreover, Wirawan, Indrawati, & Rahmanto (2017) having developed a learning media archives to improve student learning outcomes of the Vocational High School 3 of Surakarta stated a conclusion of their study that the development of instructional media digital archives is considered effective in improving student learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research conducted by Handayani, 2016 [26] was performed on a simulation of press conference subjects in Office Administration. Another similar study on the simulation method of office administration learning is Faisal's research, 2017 on handling office letters or documents at SMK Kristen 1 Surakarta; with the study results, the final average value of 79.74 with a percentage of 84.21% student activity [27].…”
Section: Simulation Learning In Office Administration Learningmentioning
confidence: 91%
“…This is on the unemployment rate that occurs in vocational school graduates, which is proven as a contributor to the highest unemployment rate reaching 11.24% because what is learned is still unable to answer the challenges of the world of work [9]. Solutions that already exist in the development of SMK media in the office sector [10]; [11] [12] in some essential competencies such as archives, documents, and digital simulations that are still not standardized and have shortcomings that are not by the needs of the industrial world, these shortcomings include [13]: (1) Some of the solutions offered are offline-based; (2) Does not describe a simulation of the world of work; (3) Requires many computers for simulation; and (4) Vulnerable to the hijacking of local server data.…”
Section: Introductionmentioning
confidence: 99%
“…Pendidikan merupakan salah satu sarana untuk menciptakan sumber daya manusia yang berkualitas. Sumber daya manusia yang berkualitas akan membangun suatu negara sehingga dapat meningkatkan kualitas suatu bangsa di era digital (Wirawan, Indrawati, & Rahmanto, 2017). Salah satu tantangan dalam pendidikan di abad ini yaitu membangun keterampilan di bidang teknologi informasi dan komunikasi.…”
Section: Pendahuluanunclassified